Environmental Disclosure on Cost of Capital: Environmental Risk as a Moderator Variable - HANINUN, Haninun; LINDRIANASARI, Lindrianasari; SARUMPAET, Susi; KOMALASARI, Agrianti; GUNARDI, Ardi (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019DO - 10.14505//jemt.v10.3(35).08, 2019)
The goal of this research is to test the effect of environmental disclosure on cost of capital. Also, to examines the environmental risk on its relationship on cost of capital. This study is derived on the stakeholder theory, legitimacy theory, and signaling theory. To implement the stakeholder theory, the companies can inform their environmental issues by disclosing their environmental management (Meng et al. 2014). They also disclose their environmental issue to fulfill both national and international regulation on environment to implement the legitimacy theory. Disclosure of environmental issue also indicates investor reliance. The larger disclosure will increase the more investor reliance (El Ghoul et al. 2011). Disclosure also indicate the signal of management to the investor. The design of this study is an explanatory research with quantitative approach. The populations in this study are the companies that listed on Indonesia Stock Exchange. The sampling technique based on purposive sampling. The data used is secondary data; consist of annual report of the company and financial report. The authenticity of this research is the first accounting study in Indonesia that examines environmental risks. The result shows that environmental risk can moderate the relationship between environmental disclosure and cost of capital.